Polyphasic and omics investigation on quorum sensing mechanisms in aquatic bacteria from tropical rainforest waterfall / Tan Wen Si - Tan, Wen Si (2017)
Quorum sensing (QS) regulates bacterial gene expressions correlating at bacterial cell population density. In this study, a total of 13 isolates were found to show QS activity with preliminary screening using bacterial QS biosensor. These 13 isolates were identified that belonged to 7 genera (Aeromonas, Cedecea, Dickeya, Enterobacter, Erwinia, Pantoea and Pectobacterium). They were identified using MALDI-TOF mass spectrometry and 16S rDNA sequence-based identification via EzTaxon database. Next, high tandem mass spectrometry was used to profile N-acylhomoserine lactone (AHL) signalling molecules produced and 11 out of 13 isolates were able to produce AHLs. Of these isolates, Enterobacter cancerogenus strain M004 was selected for further analyses due to its novelty in QS. E. cancerogenus strain M004 was found to produce 3-oxo-C6 HSL and 3-oxo-C8 HSL via mass spectrometry analysis. E. cancerogenus strain M004 was whole genome sequenced where the draft genome was 5.67 Mbp in size. Its genome data showed two QS synthase genes which were named as ecnI-1 and ecnI-2; found located at contig 7 (633 bp) and contig 2 (615 bp) respectively. Functionality of these genes was studied via heterologous gene cloning into Escherichia coli. BL21(DE3)pLysS. The ecnI-2 was found to be a non-functional QS synthase gene. The findings indicated that ecnI-1 is responsible in the production of both N-3-oxoacylhomoserine lactones in strain M004. One of the known anti-QS compounds, gallic acid was used to treat E. cancerogenus strain M004 in the transcriptome study and several genes related with QS such as fliH and betI were differential expressed. Furthermore, the biofilm assay conducted with E. cancerogenus strain M004 treated with gallic acid showed significant reduction as compared to the control (without gallic acid). To further study the functionality of QS related ecnI-1 gene, an ecnI-1 knock-out mutant was constructed using the λ red system through single-gene knock-out principle. The E. cancerogenus strain M004 luxI mutant (ΔecnI-1::Kanr) was then verified using bacterial QS biosensors followed by high resolution tandem mass spectrometry; no AHLs was detected from ΔecnI-1::Kanr mutant. Loss of function in the mutant in antibiotic resistance on chlortetracycline, erythromycin and lomeflaxin were significant as compared to wildtype via OmniLog Phenotype Microarray (PM) technology. Transcriptomic profiling was conducted to study the effect of ecnI-1 knock-out from E. cancerogenus strain M004; some genes such as cell wall/membrane/envelope biogenesis (epsJ) was down-regulated and carbohydrate transport and metabolism (glpT) was upregulated. Notable reduction in biofilm formation was observed in M004 ΔecnI-1::Kanr as compared to wildtype that further showed that ecnI-1 was involved in biofilm development. Rapid plate assay for auxin production showed a halo reddish-pink formation indicated E. cancerogenus strain M004 produced auxin. This assay was repeated with M004 ecnI-1 mutant and reduction in reddish-pink halo formation was observed. These preliminary findings indicated that QS modulate auxin production in E. cancerogenus strain M004.